Prevalence of Helicobacter pylori infection among Diabetes mellitus type two patients in Misurata-Libya (Journal of Academic Research, 2018)
Helicobacter pylori (H.pylori) is a spiral-shaped gram-negative rod. It is associated with antral gastritis, duodenal (peptic) ulcer disease, and gastric carcinoma. Other Helicobacter species that infect the gastric mucosa exist but rare.                                                                                                           H.pylori is present on gastric mucosa of less than 20% of persons under age 30 but increases in prevalence to 40-60% in persons of age 60, including individuals  who are asymptomatic, In developing countries, the prevalence of infection may be 80% or higher in adult.